Konstruktion av mätsystem till labbkvarn - Stener, Jan (2011)
This thesis is part of the project MODPULP which is a collaboration between Boliden and Luleå University of Technology. The goal is to simulate the contents of rotating mills which grind ore in the mining industry.The task of the thesis has been to develop a measurement system for measuring the power input to the contents of a mill during grinding. This has been implemented by building on an existing lab mill. The mill has been equipped with a new measurement system with associated software for data processing and calibration.The input power is calculated from the torque and rotational speed. The experiments which have been conducted show that the system is capable of measuring both the torque and rotational speed with good accuracy. Theoretical calculations and experiments suggest an uncertainty in the average torque of ±0.2 Nm (corresponding to about ±2 %). For speed measurement uncertainty is negligible.In addition to being used by Boliden for ongoing laboratory experiments, the aim is also to use data from the equipment to validate simulation results from MODPULP. Validerat; 20110908 (anonymous)